2024
DOI: 10.3390/buildings14061506
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Damping Efficiency of a Structure with Additional Viscous Dampers Based on the Shaking Table Test

Xiang Lan,
Longfei Zhang,
Baifeng Sun
et al.

Abstract: This study specifically focuses on the damping efficiency of a damped structure with additional viscous dampers. A two-layer steel frame structure with eight sets of viscous dampers is used to conduct a series of seismic simulation shaking table tests, including a non-damped structure without dampers and two damped structures with dampers placed at 1/2 and 1/6 of the beam span, respectively. By conducting these tests, the energy dissipation, force, and displacement of the damper, as well as the parameters of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…A number of researchers have adopted different methods of studying the optimization of dampers to achieve optimal control of the seismic response. Lan [35] conducted shaking table experiments on intermediate column damper systems. The results indicated that when the intermediate column is located in the middle of the span, the displacement of the viscous damper is relatively large, and the inter-story displacement of the structure can be effectively controlled.…”
Section: Introductionmentioning
confidence: 99%
“…A number of researchers have adopted different methods of studying the optimization of dampers to achieve optimal control of the seismic response. Lan [35] conducted shaking table experiments on intermediate column damper systems. The results indicated that when the intermediate column is located in the middle of the span, the displacement of the viscous damper is relatively large, and the inter-story displacement of the structure can be effectively controlled.…”
Section: Introductionmentioning
confidence: 99%